HIPCAR - cybercrime / e-Crimes : model policy guidelines & legislative texts (ITU Place des NationsCH, 2013)
Defines offences, investigation instruments and the criminal liability of key actors.
HIPCAR's objective is to assist CARIFORUM Countries in the Caribbean to harmonise their information and communication technology (ICT) policies, legislation and regulatory procedures.